ANALISIS USAHATANI KOPI POLA MONOKULTUR DAN POLA TUMPANGSELA DENGAN CABE RAWIT DI DESA SOSOKAN TABA KECAMATAN MUARA KEMUMU KABUPATEN KEPAHIANG - Nyayu Neti Arianti; Asuan Toni; Mustopa Romdhon (Jurnal AGRIBIS, 2022)
The purposes of this research were to analyze the income and efficiency of coffee monoculture farming system and intercropping system with cayenne pepper in Sosokan Taba Village Muara Kemumu Subdistrict of Kepahiang District. The research was conducted on 72 coffee farmers consisting of 45 coffee monoculture system farmers and 27 coffee farmers applying intercropping system with cayenne pepper. The result showed that the average cost of monoculture system was Rp 393.992,13/Ha/month and for the intercropping system Rp 1.057.812,31/Ha/month.Â  Although the cost incurred in the intercropping system was higher, the income earned (Rp 3,199,094,98/Ha/month) was higher than monoculture system (Rp 775,196,70/Ha/ month). The intercropping system had an efficiency value (R/C ratio) of 4.2 which was also higher than the R/C ratio of monoculture system which is only 2.9. This proves that the intercropping system is more profitable than the monoculture system.Â Keywords : coffee farming, monoculture, intercropping,.